Popularity and worldwide reach of targeted, evidence-based internet streaming video interventions focused on men’s health topics - Zaila, Kassandra E. (Transl Androl Urol, 2020)
Streaming video has emerged as a dominant content-delivery medium for healthcare information, with over 30 million visitors daily to the YouTube platform alone. Videos related to men’s health have proliferated, but content produced by trained health care providers remains scarce. We evaluated educational YouTube streaming videos created in collaboration with a large, university-based health system focused on male factor infertility, men’s health, and Peyronie’s disease, uploaded during 2016–2018. All videos featured a board-certified urologist with fellowship training in andrology. Using YouTube’s native analytics tools, we extracted data on views, engagement, and geographic reach through 8/2019. We obtained data for streaming videos on male infertility (n=3), general men’s health (n=2), and Peyronie’s disease (n=1). Video length ranged from 29 to 51 min, with a mean video duration of 39 min 41 sec. Actual mean watch time by viewers ranged from 3:45 to 8:30. The total view count was 646,684, with a watch time of nearly 3 million mins, reaching viewers in 47 countries. Fifty-three percent of watch time was on a mobile device and 33% on a personal computer. As patients increasingly turn to the internet for health information, health systems and physicians may wish to leverage high impact social media platforms such as YouTube to share evidence-based content. This study highlights the impressive reach a health system-sponsored video intervention using YouTube can have in sharing accurate video content related to a diverse range of men’s health topics. This is the first health systems-based streaming-video intervention to leverage the video streaming and social media platform YouTube, to facilitate sharing reputable, high quality, and evidence-based men’s health content.